2013
DOI: 10.1002/14651858.cd006964.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for communicating contraceptive effectiveness

Abstract: These trials varied greatly in the types of participants and interventions to communicate contraceptive effectiveness. Therefore, we cannot say overall what would help consumers choose an appropriate contraceptive method. For presenting pregnancy risk data, one trial showed that effectiveness categories were better than pregnancy numbers. In another trial, audiovisual aids worked better than the usual oral presentation. Strategies should be tested in clinical settings and measured for their effect on contracep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 55 publications
0
33
0
4
Order By: Relevance
“…Relative effectiveness -as well as the likelihood of side-effects -can be hard to convey in counselling. [21] Job aids may facilitate this, but some recommend simply discussing contraceptive options in order of effectiveness from highest (LARCs) to lowest. [22,23] This 'LARC-first' approach to counselling extends, in some settings, to LARCs being promoted explicitly as first-line contraception and other methods as second-tier.…”
Section: Discussionmentioning
confidence: 99%
“…Relative effectiveness -as well as the likelihood of side-effects -can be hard to convey in counselling. [21] Job aids may facilitate this, but some recommend simply discussing contraceptive options in order of effectiveness from highest (LARCs) to lowest. [22,23] This 'LARC-first' approach to counselling extends, in some settings, to LARCs being promoted explicitly as first-line contraception and other methods as second-tier.…”
Section: Discussionmentioning
confidence: 99%
“…71 This review concluded that audio-visual aids were more effective than oral communication, and that presenting contraceptive efficacy with respect to categories of effectiveness, rather than exact numbers, was preferable. We suggest the WHO tiered counseling chart as a model, which has been shown to effectively improve knowledge of relative contraceptive efficacy.…”
Section: What Are Best Practices For Contraceptive Counseling?mentioning
confidence: 99%
“…Despite high rates of unintended pregnancy and sexually transmitted infection (STI) in the United States, and public health goals to reduce prevalence [1], surprisingly little research has identified effective counseling approaches for use in clinical settings to influence sexual risk behavior [2, 3]. A number of theory-driven interventions to reduce HIV/AIDS acquisition and transmission have been successful in community and clinic settings, but generally are implemented with specially trained study staff [4,5].…”
Section: Introductionmentioning
confidence: 99%